2005
DOI: 10.1088/0953-2048/18/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Upper critical field, irreversibility field, and critical current density of powder-in-tube-processed MgB2/Fe tapes

Abstract: We fabricated pure and SiC-added MgB2/Fe composite tapes using a MgH2 starting powder and applying heat treatments at 600–900 °C and systematically investigated their superconducting properties. For both the pure and SiC-added tapes, the critical temperature (Tc) increased with increasing heat-treatment temperature due to the improved crystallinity of MgB2.The SiC addition decreased the Tc but increased the slope of the Bc2–T and Birr–T curves, d Bc2/d T and d Birr/d T, for all heat-treatment temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
45
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 14 publications
10
45
1
Order By: Relevance
“…It was reported that, for the SiC-added tape, the a-axis length shrank, while the c-axis did not change due to the substitution of the carbon from SiC powder for boron. 9 Similar changes of the a-and c-axis lengths were also observed for C 6 H 6 -, C 10 H 8 -, and C 4 H 4 S-added tapes, although the decrease of the a-axis length is almost independent of the amount of C 6 H 6 . This result indicates that the substitution of carbon for boron also occurs in the aromatic hydrocarbon-added tapes.…”
supporting
confidence: 65%
“…It was reported that, for the SiC-added tape, the a-axis length shrank, while the c-axis did not change due to the substitution of the carbon from SiC powder for boron. 9 Similar changes of the a-and c-axis lengths were also observed for C 6 H 6 -, C 10 H 8 -, and C 4 H 4 S-added tapes, although the decrease of the a-axis length is almost independent of the amount of C 6 H 6 . This result indicates that the substitution of carbon for boron also occurs in the aromatic hydrocarbon-added tapes.…”
supporting
confidence: 65%
“…This result can be explained by the improved crystallinity of the MgB 2 core, indicating that the grain size increases with sintering temperature. 21 The FWHM behavior of long CNT doped wire as a function of sintering temperature was similar to that of pure wire. However, FWHMs of short CNT doped wire increased with annealing temperature.…”
Section: Results and Disscussionmentioning
confidence: 71%
“…The resistance measurements were carried out on Physical Properties Measurement System (PPMS) up to 9 T using small pieces of MgB 2 core after peeling off the Fe sheath or on a 20 T magnet using Fe sheathed MgB 2 tapes. [22] The transport I c at 4. is an indication of the carbon substitution for boron, [18] which is further proved by the depression of the critical transition temperature (T c ) of the C 60 doped samples. The C substitution to B site has a great impact on the carrier density and impurity scattering.…”
mentioning
confidence: 99%
“…[20] Figure 2 [22] For instance, at 20 K, H irr was nearly 10 T for C 60 doped MgB 2 tapes sintered at 800 °C. This is in accordance with XRD analysis that C has been substituted into MgB 2 lattice.…”
mentioning
confidence: 99%